In situ production of core and intact bacterial and archaeal tetraether lipids in groundwater. (December 2018) - Ding, Su; Kohlhepp, Bernd; Trumbore, Susan; Küsel, Kirsten; Totsche, Kai-Uwe; Pohnert, Georg; Gleixner, Gerd; Schwab, Valérie F.
Highlights: Core and intact polar GDGTs in groundwater are reported. These can be used to trace soil input to groundwater. Both bacteria- and archaea-derived GDGTs were mainly produced within groundwater. Cycling rate of GDGTs in groundwater is lower than in surface soils. Abstract: Groundwater ecosystems host diverse and complex microbial communities that play important roles in the biogeochemical processing of organic matter and in the maintenance of drinking water quality. Here we investigated the microbial community in suspended particulate matter (SPM) of biogeochemically distinct groundwaters (Hainich Critical Zone Exploratory) by analyzing branched and isoprenoid glycerol dialkyl glycerol tetraethers (GDGTs) from bacteria and archaea, respectively. The contributions of those lipids derived from dead and living organisms were determined by analyses of the core lipid distributions of core and intact polar GDGTs. We compared the groundwater GDGT distributions to the ones from soils of potential recharge areas and with archaeal 16S rRNA-gene based community reconstructions to estimate their origin in these terrestrial subsurface environments and thus their potential use for evaluating soil inputs into groundwater. In soils, the relative abundance of intact polar branched GDGTs (brGDGTs) was lower than that of isoprenoid GDGTs (isoGDGTs; 2% vs 5% of total GDGTs), while the opposite trend (71% vs 22% of total GDGTs) was observed in the core lipid pools. This supports previous observations that soil brGDGT-producing bacteria might be more active and thus have higher regeneration rates than the isoGDGT-producing archaea. We found similar trends in the groundwater that might indicate higher activity (i.e., cell division) of brGDGT-producing bacteria than of isoGDGT-producing archaea. The higher relative abundance of the hexamethylated brGDGT in the groundwater SPM (mean 65 ± 9%, n = 5) than in soils (mean 16 ± 7%, n = 22) indicated an in situ origin of brGDGT-producing bacteria. Higher contributions of penta- and tetra-methylated brGDGTs, which suggested some inputs from soil bacteria, was only detected in two out of seven groundwater samples. The strong correlation between core and intact polar isoGDGTs (R 2  = 0.99, n = 7) in groundwater SPM indicated low disturbance (e.g., surface inputs) and suggested indigenous archaeal communities in the groundwater. This was supported by the results from a previous 16S rRNA-gene study that detected distinct archaeal groups in soils and groundwater. This first GDGT study in groundwater demonstrated that even dynamic karstic subsurface environments host an indigenous bacterial and archaeal community that is adapted to the living conditions. Furthermore, fast recharge events are likely detectable using tetraether lipids from the soil microbial community.